Violation of language decity in Nikita Mirzani's podcast and implications on indonesian language learning - Zulyalita, Winy Warda (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research examines language politeness violations that occur in Nikita Mirzani's podcast on her YouTube channel. This study uses a qualitative method that aims to describe violations of politeness in language. The data in this study are politeness in the conversation spoken by Nikita Mirzani. The data source used was in the form of speeches spoken by Nikita Mirzani with several guest stars who were invited to the Nikita Mirzani podcast. Data was collected using the observing and note-taking techniques, namely by listening to videos that were used as research data and then recording the findings of the violations that occurred. Based on the data found, it shows that in Nikita Mirzani's podcast there are language violations, namely the maxims of wisdom, generosity, appreciation, simplicity, agreement and sympathy. Apart from being carried out by Nikita Mirzani herself, violations of maxims were also found by sources or guest stars who were invited to Nikita Mirzani's podcast